Assessment of Healthcare Providers’ Acceptance of Telemedicine Consultation in Sarawak - Kelvin, Siaw Yun Ted (Unimas, 2024)
In order to provide information, education, medical consultation, diagnosis, treatment, support, and governance, Malaysia formed the Telemedicine Blueprint in 1997. The COVID-19 epidemic enhanced consumer knowledge of telemedicine, but patients and healthcare providers still have low levels of adoption, according to the Malaysian Medical Council in year 2020. Despite the advantages of using such technology, healthcare personnel under utilize it due to several factors. Based on the background and problems of acceptability towards telemedicine, no market data for Sarawak is available, and has not yet been established. Besides, there are no user perspectives from healthcare providers that are found to match with telemedicine adoption based on the Sarawak context, and there are no guidelines based on data-riven (current-status in Sarawak) decisions. The telemedicine might able to leverage the issues of delayed diagnostic and the needs of medical consultations, yet the alarming still persist in Sarawak due to lack of medical officers in primary centers. As a result, the experiment aims to estimate the acceptability. The initial goal of this study is to identify the demographics and consumer attitudes towards telemedicine in Sarawak among healthcare providers. Next, determine consumers’ perceivance of telemedicine in Sarawak. Finally, to demonstrate the broad correlations between consumer attitude and intention. Cross sectional study is embarked, 164 sample are collected from healthcare providers. Healthcare professionals of Sarawak's four largest cities, Kuching, Sibu, Bintulu and Miri, are the targeted. Questionnaires based on the TAM models are constructed to evaluate and forecast the acceptability of telemedicine. The association was examined using PLS-SEM. Throughout the study, four variables were shown to have a significant link in the TAM (6 hypothesis accepted out of 11). Researchers reviewed the significant variables related to the intention to use telemedicine systems to assist healthcare business stakeholders in understanding how potential users embrace and adopt such a system. The significant of the study, might act as initial data platform to both the government and privates for the better understanding (knowledge and research) of how consumers can use an efficient telemedicine system in healthcare business settings from the perspectives of healthcare providers.